ESWL EFFECTIVENESS FOR LOWER POLE KIDNEY STONES - Sholihin, Riza Mazidu; Soetojo, Soetojo; Muris, Haviv (Indonesian Journal of Urology, 2019)
Objective: To describe the profile of lower pole kidney stone patients who underwent Extracorporeal Shock Wave Lithotripsy (ESWL) and the clearance rate of ESWL for lower pole kidney stones at Soetomo General Hospital from 2012 to 2016. Material & Methods: This research design was analytical retrospective, lower pole kidney stone patients who underwent ESWL in Soetomo General Hospital from 2012 to 2016 who fulfill inclusion criteria become samples in this research. Samples were divided into two group, stone size <15 mm and 15-20 mm. Results: Total samples in this study were 128, consist of 81 males and 47 females. The age average was 48 ± 11.124. The stone size average was 9.5 ± 4.5 mm consisted of 109 patients with stone size <15 mm and 19 patients with stone size 15-20 mm. There were 119 single lower pole kidney stones and 9 multiple ones. From all patients, 77 patients (60.2%) were stones free and the rest (39.8%) were not. Stone free rate for lower pole kidney stones was higher in stone size <15 mm compared with 15-20 mm, 65.2% and 31.5% respectively. Statistical analysis with Chi-square showed significant ESWL clearance rate difference between lower pole kidney stone size <15mm group and 15-20 mm (p<0.05). Conclusion: ESWL was a safe option for lower pole kidney stones with high success rate. There was significant relationship between stone size and stone clearance rate. ESWL was effective for lower pole kidney stones size <15 mm.